ACERCA DE LA CONSECUTIO TEMPORUM EN LAS PROPOSICIONES CONSECUTIVAS - Sánchez-Lafuente Andrés, Ángela; García de la Calera Martínez, Roberto (Myrtia, 1997)
It comes to the conclusion that the Non-Perfect aspect is the Non-Marked in the past process clauses. It is emphasized that the Subjuntive of the consecutive clauses has true modal value, it has no time indicators although the speaker of the message can use perfect aspect or periphrastic forms to mark the end or the beginning of the action, its frequency is optional since it could be used Non-Perfect aspect verbal forms.